THE INFLUENCE OF THE IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS, GOVERNMENT ACCOUNTING SYSTEMS AND HUMAN RESOURCES COMPETENCE ON THE QUALITY OF GOVERNMENT FINANCIAL REPORTS IN BAKORWIL V, EAST JAVA PROVINCE - Khotimah, Hosnol; Suharsono, Riyanto Setiawan; Ibna Kamelia Fiel Afroh (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the influence of the implementation of Standard Accountancy Government (SAP), the government accountancy system, and human resource competence on the quality of government financial reports in the Bakorwil V region of East Java Province. In an era of governance that demands transparency and accountability, the quality of financial reports becomes very important. Method: The research method used is quantitative with a survey approach, involving BPKAD employees from several regencies as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. Results: The research results show that SAP implementation and the government accountancy system have a positive and significant influence on the quality of financial reports. Additionally, human resource competence also contributes to improving the quality of financial reports. Novelty: These findings emphasize the importance of improving accounting standards, refining the accounting system, and developing employee competencies to achieve high-quality financial reports. This research is expected to contribute to the development of governmental accounting knowledge and serve as a reference for better regional financial management policies.